Hypoxia-Inducible Factor-1α in Smooth Muscle Cells Protects Against Aortic Aneurysms—Brief Report. Issue 11 (November 2016) - Imanishi, Masaki; Chiba, Yoichi; Tomita, Noriko; Matsunaga, Shinji; Nakagawa, Toshitaka; Ueno, Masaki; Yamamoto, Kazuhiro; Tamaki, Toshiaki; Tomita, Shuhei
Abstract : Objective—: The purpose of this study was to determine the role of smooth muscle cell–derived hypoxia-inducible factor-1α (Hif-1α) in the pathogenesis of aortic aneurysms. Approach and Results—: Control mice and smooth muscle cell–specific hypoxia-inducible factor-1α–deficient mice were infused with β-aminopropionitrile for 2 weeks and angiotensin II for 6 weeks to induce aortic aneurysm formation. Mutant mice experienced increased levels of aneurysm formation of the thoracic or abdominal aorta with more severe elastin disruption, compared with control mice. Smooth muscle cell–specific hypoxia-inducible factor-1α deficiency did not affect matrix metalloproteinase-2 activity; however, the activity of lysyl oxidase and the levels of tropoelastin mRNA in the angiotensin II– and β-aminopropionitrile–treated aortae, associated with elastin fiber formation, were suppressed. Furthermore, we observed reduced volumes of mature cross-linked elastin in the thoracoabdominal aorta after treatment with angiotensin II and β-aminopropionitrile. Conclusions—: Deficiency of smooth muscle cell–derived hypoxia-inducible factor-1α augments aortic aneurysms, accompanied by disruption of elastin fiber formation, but not changes of elastin fiber degradation. Abstract : Supplemental Digital Content is available in the text.